First Trimester Contingent Screening for Aneuploidies with Cell-Free Fetal DNA in Singleton Pregnancies – a Swiss Single Centre Experience - Proto, Alice; Trottmann, Fabienne; Schneider, Sophie; Amylidi-Mohr, Sofia; Badiqué, Florent; Risch, Lorenz; Surbek, Daniel; Raio, Luigi; Mosimann, Beatrice (Geburtshilfe und Frauenheilkunde, 2024)
Switzerland was amongst the first countries to offer cell-free fetal DNA (cffDNA) testing covered by the health insurance to pregnant women with a risk ≥ 1:1000 for trisomies at first trimester combined screening (FTCS). The aim of this study is to evaluate the implementation of this contingent model in a single tertiary referral centre and its effect on gestational age at diagnosing trisomy 21.Between July 2015 and December 2020 all singleton pregnancies at 11–14 weeks of gestation without major fetal malformation were included and stratified according to their risk at FTCS. Statistical analysis was performed by GraphPad Version 9.1 for Windows.4424 pregnancies were included. Of 166 (3.8%) pregnancies with a NT ≥ 3.5 mm and/or a risk ≥ 1:10 at FCTS, 130 (78.3%) opted for direct invasive testing. 803 (18.2%) pregnancies had an intermediate risk, 692 (86.2%) of them opted for cffDNA first. 3455 (78.1%) pregnancies had a risk < 1:1000. 63 fetuses were diagnosed with trisomy 21, 47 (74.6%) directly by invasive procedures after FTCS, 16 (25.4%) by cffDNA first.Most women choose cffDNA or invasive testing as second tier according to national guidelines. Despite the delay associated with cffDNA testing after FCTS, 75% of all trisomy 21 are still diagnosed in the first trimester with this contingent screening model.
Keywords: first trimester screening; trisomies; cell-free fetal DNA; non-invasive prenatal testing